MANAJEMEN STRATEGI PENINGKATAN MUTU TENAGA PENDIDIK DI MTs NEGERI MODEL PURWOKERTO - Ramelan Ramelan (IAIN Purwokerto, 2019)
Strategic management in the world of education is something relatively new. This is because the success of profit institutions to implement strategic management to achieve their goals. MTs Negeri Model Purwokerto is a state educational institution tat has a clear future education orientation. The institution is a leading educational institution with full of academic and non-academic achievement learners. The teachers in this institution are strictly selected teachers. This study aims to describe and analyze strategic management in improving the quality of teachers in MTs Negeri Model Purwokerto, ranging from environmental analysis, strategic formulation, strategic implementation until evaluation and strategic supervision in improving teacher quality. This research is a qualitative descriptive research, the research location take place in MTs Negeri Model Purwokerto Banyumas Regency. Data collection techniques used are observation, interviews, and documentation. Data analysis used in this study is qualitative data analysis, using three activity flow, data reduction, data presentation and verification/drawing conclusion, and SWOT analysis. Verification of data validity using data triangulation technique. The results showed that: Periama, environmental analysis conducted by MTs Negeri Purwokerto Model for improving the quality of educator is SWOT analysis which produce program or activity according to education institution needs. Second, the strategic formulation used by MTs Negeri Model Purwokerto is done by compiling the vision, mission, and objectives of the madrasah made by the team of formulation of School Work Plan (RKS). The strategic formulation done by MTs Negeri Model Purwokerto for the improvement of teacher quality with teacher recruitment program, guidance and teacher development. Third, in order to get competent and highly committed teacher candidates, the strategy taken by MTs Negeri Model Purwokerto to improve teacher quality is to recruit at any time according to need, with tight selection without KKN elements. While the guidance and empowerment of teachers conducted by the organizing committee. Fourth, evaluation and strategic supervision of MTs Negeri Model Purwokerto. There are two kinds of individual supervision by head of madrasah, vice principal of curriculum affair, senior educator, and Supervisor. While group supervision is held with teachers of one subject cluster in weekly and monthly coordination meetings and MGMP